2013
DOI: 10.1371/journal.pone.0065932
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang 1 Intronic Binding Sequences and Splicing Elicit Intron-Mediated Enhancement of Ubiquitin C Gene Expression

Abstract: In a number of organisms, introns affect expression of the gene in which they are contained. Our previous studies revealed that the 5′-UTR intron of human ubiquitin C (UbC) gene is responsible for the boost of reporter gene expression and is able to bind, in vitro, Yin Yang 1 (YY1) trans-acting factor. In this work, we demonstrate that intact YY1 binding sequences are required for maximal promoter activity and YY1 silencing causes downregulation of luciferase mRNA levels. However, YY1 motifs fail to enhance ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 62 publications
2
37
2
Order By: Relevance
“…This is not in contrast with the previous evidence that transfection of Sp1/Sp3 raises the expression of the intron-retaining and intron-less constructs because the enhancement observed could be due to Sp1/Sp3 interaction with the upstream binding sites (contained in both constructs), previously identified by Marinovic et al [31]. On the other hand, when the two YY1 intronic binding sites were mutated, a statistically significant drop in luciferase activity was observed [39].…”
Section: Ubc Transcriptional Regulationcontrasting
confidence: 84%
See 2 more Smart Citations
“…This is not in contrast with the previous evidence that transfection of Sp1/Sp3 raises the expression of the intron-retaining and intron-less constructs because the enhancement observed could be due to Sp1/Sp3 interaction with the upstream binding sites (contained in both constructs), previously identified by Marinovic et al [31]. On the other hand, when the two YY1 intronic binding sites were mutated, a statistically significant drop in luciferase activity was observed [39].…”
Section: Ubc Transcriptional Regulationcontrasting
confidence: 84%
“…PPAR binding site was identified by Kim [36]. YY1 intronic binding sites were identified by Bianchi et al [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variant expressed slightly more EmGFP than UBCs, presumably due to improved nuclear export from splicing, but significantly less than UBC (Figure 4C ). These results are consistent with a follow-up study on the UBC promoter fragment intron, which found that its enhancer activity was fully dependent on its position within the intron ( 15 ). This behavior, termed intron-mediated enhancement, is poorly understood.…”
Section: Resultssupporting
confidence: 91%
“…TGCTCGAATGAACACTCTGG TCCTCTGTCAGCATCACCTG according to the manufacturer's instructions, as described in [26]. Briefly, HeLa cells were treated with 80 lM NaAsO 2 , 20 lM MG132 for 4 h at 37°C or left untreated (control).…”
Section: Chromatin Immunoprecipitation and Pcr Of Chromatin Templatesmentioning
confidence: 99%